Hubungan Kredibilitas Youtube Beauty Vlogger “Miss X” Dengan Minat Belajar Tata Rias Wajahpada Mahasiswa S1 Tata Rias Angkatan 2021-2022 Universitas Negeri - Ayu Jusrianti; Mari Okatini Armandari; Neneng Siti Silfi (Journal on Education, 2025)
This research was created with the aim of obtaining data on the credibility of Beauty Vlogger Miss Jakarta. This research uses quantitative correlational methods. The population of this study were all undergraduate students of Cosmetology class 2021-2022, Jakarta State University. The sampling technique used in this research was purposive sampling. The sample criteria in this study were undergraduate students in Cosmetology class 2021-2022 who knew Beauty Vlogger Miss X, were subscribers or followers of YouTube Miss X, and used YouTube Miss So, the sample in this research is the 2021-2022 undergraduate students of Jakarta State University, namely 53. The data analysis techniques used are associative quantitative techniques, analysis requirements tests, data normality tests, linearity tests. The results of this research show that there is a positive and significant relationship between the credibility of YouTube Beauty Vlogger Miss The majority of interest in learning facial make-up is in the high category, namely 56.6%. And according to the research results, it shows that the majority of Beauty Vlogger Miss X's credibility is in the low category, namely 58.2%. So, it can be seen that the credibility of Beauty Vlogger Miss